Interhemispheric comparison of the ionosphere and plasmasphere total electron content using GPS, radio occultation and ionosonde observations. Issue 6 (15th September 2021) - Habarulema, John Bosco; Okoh, Daniel; Bergeot, Nicolas; Burešová, Dalia; Matamba, Tshimangadzo; Tshisaphungo, Mpho; Katamzi-Joseph, Zama; Pinat, Elisa; Chevalier, Jean-Marie; Seemala, Gopi
Abstract: We present a comparison of the ionosphere and plasmasphere total electron content over nearly geomagnetic conjugate locations Pruhonice ( 50.0 ° N, 14.6 ° E; 45.7 ° N geomagnetic), Czech Republic and Hermanus ( 34.4 ° S, 19.2 ° E; 42.3 ° S geomagnetic), South Africa during the low solar activity period of 2009–2010. The bottomside ionosphere, topside ionosphere and plasmaspheric contributions to the total electron content (TEC) derived from the Global Positioning System (GPS) observations are separately estimated from ionosonde and Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) radio occultation data. Over the ionosonde location, COSMIC electron density (Ne) profiles are considered when the maximum height of the F2 layer (hmF2) lies within spatial resolutions of 4.5 ° × 4.5 ° in latitudes/longitudes, and the Ne profile does not exceed 10 ° . For the first time, we have statistically quantified the topside ionosphere contribution to GPS TEC based on radio occultation data and revealed that it accounts for about 50% of the TEC during low solar activity periods. Finally, we have demonstrated that the determination of electron content contribution at different altitudes is important for understanding ionospheric storm mechanisms during space weather events especially geomagnetic storms.